A pilgrim with a poet's soul George A. Simons (1874-1952) : a pioneer missionary in Russia and the Baltic States (1907-1928) - Kimbrough, S. T. 1936- (Pickwick Publications, 2019)
"George Albert Simons (1874-1952) of New York State was the first and only American missionary of the Methodist Episcopal Church appointed as superintendent of the Russia Mission. He arrived in St. Petersburg in 1907 during the reign of the Tsar Nicholas II. He succeeded in registering the first Methodist congregation in St. Petersburg in 1912, based on the registration of the Methodist congregation in 1906 in Kaunas, Lithuania, then part of the Russian Imperial Empire. Simons soon mastered the Russian language, and he established numerous congregations in and around St. Petersburg and as far East as Marinsk. A tireless worker, he developed an extensive publishing program of Methodist resources: hymnals, journals, liturgies, discipline, and beliefs, etc. In 1918, after the Bolshevik Revolution, he was forced to leave Russia. In 1920, he was reassigned to the Baltic States with headquarters in Riga, Latvia, with some continuing responsibilities for the Russia Mission. In Riga, he established an institute to train clergy, continued his publishing program, and procured numerous properties for church buildings. Without the efforts of Simons, Methodism in Russia and the Baltic States would be but a shadow of what it is today. The foundation he laid helped make possible the rebirth of Methodism in these countries after the demise of Communism. He was indeed a pilgrim, who journeyed to a sacred place, Russia, to plant seed for the growth of Methodism. He had the soul of a poet as can be seen in his vast amount of poetry and hymns that bear witness to his theology and experience in Russia."--Publisher
Keywords: Simons, George Albert -- 1874-1952; Methodist Episcopal Church; Geschichte 1907-1928; Mission; Russland; Baltikum; Simons, George A. / 1874-1952; Methodist Episcopal Church / Clergy / Biography; Missionaries / Russia / Biography; Missionaries / Baltic States / Biography; Methodist Church / Russia / History; Methodist Church / Baltic States / History; Russia / Church history; Baltic States / Church history; Biografie